A critique of social marketing in the non-profit development sector - Fourie, L. M. (Koers, 2009)
In its struggle to find funding, non-profit organisations world-wide are increasingly using social marketing strategies. This approach potentially influences non governmental organisations (NGOs) and community based organisations (CBOs) in their communication with their “clients”, i.e. those persons and com-munities in need of development. Marketing strategies con-sequently become instruments in achieving social development, with as main premise that behaviour could be changed by means of persuasive, top-down communication. Social marketing, with its roots in marketing, has a strong focus on persuasion and favours top-down communication rather than dialogical communication strategies suggested by the par-ticipatory development communication approach. It is also questionable whether social marketing can be equated with the principles of a Biblically informed approach to communication. With these questions in mind, this article discusses Biblical views on communication and the participatory development communication approach. A critique of the social marketing approach is then offered. It is argued here that there is no clear-cut answer as to whether social marketing could be described as participatory. What is clear is that there are many different views on social marketing, as is the case with participatory approaches. It would thus seem more correct to place social marketing on a participation continuum, rather than to define it as being participatory and thus per definition ethical or not. Finally, a number of suggestions are made which could bring it more in line with the participatory communication approach as well as Biblical principles on com-munication.